PEMINDAHAN HAK ATAS KEKAYAAN YAYASAN MENURUT UNDANG-UNDANG NOMOR 16 TAHUN 2001 JO UNDANG-UNDANG NOMOR 28 TAHUN 2004 TENTANG YAYASAN - M. Rizky Faizha Putra; T. Keizerina Devi Azwar; Ramli Siregar (TRANSPARENCY, 2013)
The transfer of property rights foundation in regard to the provisions set forth in Law No. 16 year 2001 yo Act No. 28 of 2004 ("the Law Foundation"). The principle is based on the provisions stipulated in the Law on Foundations, the transfer of property rights by the Foundation with the approval of the Foundation Board of Trustees Foundation. Other terms and conditions relating to this notice shall further provisions in the Articles of Association of the Foundation. for example, who is authorized to represent the Board and how the shape of the approval granted by the Trustees. The research was conducted using the method of normative legal research or legal research literature, the data used are the primary legal materials, secondary, and tertiary, while the data collection is done with the study of literature (library researh). Based on the results of the study authors that the management of the property was also deemed necessary foundation rearrangement and self improvement. Management of the Foundation in a professional and efficient with the implementation of the principle of transparency in all its operations is a necessity at the present time. Foundation in the act represented by its officials. Monitoring of the board needs to be done because the board is difficult to interpret what the wishes of the stakeholders. This gives an opportunity for the Board to run the country or company based commentary on what is desired by stakeholders. Supervision is done by limiting the authority of the Board. Keywords: Transfer of property rights, the foundation   Keywords: Pemindahan Hak Atas Kekayaan, Yayasan